2012
DOI: 10.1097/hcm.0b013e31826fe340
|View full text |Cite
|
Sign up to set email alerts
|

Factors Impacting Career Satisfaction of Hospitalists

Abstract: A study was undertaken to examine various factors that impact career satisfaction of hospitality. This study used data collected by the Center for Studying Health System Change's 2008 Health Tracking Physician survey. The 2008 HTP data set consisted of 4720 physicians belonging to the American Medical Association, of which 206 identified themselves as hospitalists. Results suggested that 41% of hospitalists were very satisfied with their careers in medicine. More than 26% of the hospitalists were 53 years or o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 33 publications
1
2
0
Order By: Relevance
“…This finding is intuitive and has been replicated for other specialties in this survey, including hospitalists, 18 pediatricians, 19 and psychiatrists. 20 The correlation matrix in Table 3 shows that high-quality care was negatively correlated with Medicare patients (À0.12, P < .05).…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…This finding is intuitive and has been replicated for other specialties in this survey, including hospitalists, 18 pediatricians, 19 and psychiatrists. 20 The correlation matrix in Table 3 shows that high-quality care was negatively correlated with Medicare patients (À0.12, P < .05).…”
Section: Discussionsupporting
confidence: 57%
“…5,6 Recent studies of physician satisfaction using HSC data have flagged significant relationships at P .07 and P .10. [18][19][20] For consistency's sake, the higher alpha () is used here. Table 1 shows that obstetrician-gynecologists were largely satisfied with their careers in medicine; 45.2% were ''somewhat satisfied'' and 35.2% were ''very satisfied.''…”
Section: Discussionmentioning
confidence: 99%
“…Physician job attitudes are a longstanding strategic concern for hospitals and professional organizations [ 14 ]. Studies have found significant relationships between physician job attitudes and quality of patient care, physician errors, [ 15 ] turnover, [ 16 ] patient satisfaction, [ 17 ] and adherence to formal care guidelines [ 18 ]. Studies also have shown positive relationships between research involvement and job attitudes among physicians in academic practice [ 19 ].…”
Section: Introductionmentioning
confidence: 99%